2006
DOI: 10.3348/kjr.2006.7.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal Epidural Steroid Injection for Lumbosacral Radiculopathy: Preganglionic versus Conventional Approach

Abstract: ObjectiveThe present study was undertaken to evaluate the effectiveness of transforaminal epidural steroid injection (TFESI) with using a preganglionic approach for treating lumbar radiculopathy when the nerve root compression was located at the level of the supra-adjacent intervertebral disc.Materials and MethodsThe medical records of the patients who received conventional TFESI at our department from June 2003 to May 2004 were retrospectively reviewed. TFESI was performed in a total of 13 cases at the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 17 publications
2
58
0
4
Order By: Relevance
“…Another study done by Hee Sun Jeong and Joon Woo Lee on 239 patients of lumbar disc prolapse was conducted consisting of 106 males and 133 females [13]. The average age of patient was 49.8 (13-82) years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study done by Hee Sun Jeong and Joon Woo Lee on 239 patients of lumbar disc prolapse was conducted consisting of 106 males and 133 females [13]. The average age of patient was 49.8 (13-82) years.…”
Section: Discussionmentioning
confidence: 99%
“…Macnab et al, (1971) described Selective Nerve Root Blocks (SNRBs) as a diagnostic test to evaluate patients with negative imaging studies and clinical finding of nerve root irritation [9]. Since then many studies have reported the efficacy of this technique through the transforaminal route [10][11][12][13][14][15]. Warr et al, (1972) reported good results in 63% of their series of 500 patients [16], in whom epidural medication of 40 ml of 0.75% lignocaine mixed with steroid was injected through L3-L4 interspace in the epidural space.…”
mentioning
confidence: 99%
“…The procedure was performed by the preganglionic approach described by Le et al (16,17). They described that for the preganglionic approach, the landmark for needle insertion was slightly lateral to the pars interarticularis on the oblique view, and at the neural foramen near the nerve root impingement site at the supra adjacent disk level on the posteroanterior view.…”
Section: The Proceduresmentioning
confidence: 99%
“…TFESIs were performed in the operation theatre equipped with a planar fluoroscope (Siemens TM , Munich, Germany) while the patients were prone. After sterile preparation, draping, and local anesthesia with one per cent lidocaine, a 9-cm long, 21- (16,17) described that for the preganglionic approach, the landmark for needle insertion was slightly lateral to the pars interarticularis on the oblique view, and at the neural foramen near the nerve root impingement site at the supra adjacent disk level on the posteroanterior and oblique view ( Figure 1A, B). Then 0.5 mL of bupivacaine HCl (Marcaine Spinal 0.5% Heavy TM ; AstraZeneca, Istanbul) was injected (~1 min), followed by 40 mg (1 mL) of methylprednisolone acetate suspension [Depomedrol TM Eczacibasi Ilac San., Luleburgaz, Kirklareli].…”
Section: The Proceduresmentioning
confidence: 99%
See 1 more Smart Citation